The political economy of the 'just transition'. Issue 2 (27th February 2013) - Newell, Peter; Mulvaney, Dustin
<x xml:space="preserve">Abstract</x> This paper explores the political economy of the 'just transition' to a low carbon economy. The idea of a 'just transition' increasingly features in policy and political discourse and appeals to the need to ensure that efforts to steer society towards a lower carbon future are underpinned by attention to issues of equity and justice: to those currently without access to reliable energy supplies and living in energy poverty and to those whose livelihoods are affected by and dependent on a fossil fuel economy. To complicate things further this transition has to be made compatible with the pursuit of 'climate justice' to current and future generations exposed to the social and ecological disruptions produced by increasing concentrations of greenhouse gas emissions in the atmosphere. Here we seek to identify and analyse the immensely difficult political trade‐offs that will characterise collective attempts to enact and realise a just transition. We explore procedural and distributional aspects of energy politics and practice in particular as they relate to the just transition: energy access for those who do not have it; justice for those who work within and are affected by the fossil fuel economy; and attempts to manage the potential contradictions that might flow from pursuing energy and climate justice simultaneously.